Menschenrechte und Menschenwürde: Vier thematische Einblicke. Vadian Lectures Band 5 - Meier Kressig, Marcel; Lindenau, Mathias (transcript, 2019)
This volume deals with questions of human rights and human dignity from different perspectives.